2003
DOI: 10.1111/j.1742-1241.2003.tb10480.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin D3 on Insulin Secretion and Peripheral Insulin Sensitivity in Type 2 Diabetic Patients

Abstract: SUMMARYThe aim of this study was to evaluate the effect of vitamin D3 supplementation on insulin secretion and insulin resistance. Ten females with type 2 diabetes being treated with oral hypoglycaemic agents and with normal serum and urine calcium levels were enrolled in the study. The study was conducted in March, when levels of vitamin D are lowest in our region. The level of plasma 25(OH)D was measured (normal range in winter 25–120 nmol/l). The first (FPIS) and second (SPIS) phases of insulin secretion we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Regarding insulin secretion, beta cells express both VDR and 1 alpha-hydroxylase (Cyp27b1), which catalyzes the activation of 25OHD into 1,25(OH) 2 D, denoting the cell-intrinsic role for VDR [ 75 ]. Nevertheless, even if the relationship between vitamin D levels and islet function is significant, whether vitamin D supplementation can directly ameliorate insulin secretion in humans remains uncertain because intervention clinical trials have reported mixed results [ 75 , 76 , 77 , 78 ]. As regards the ubiquitous expression of VDR, and, in particular, in insulin-sensitive tissues, a study analyzing human and rodent data showed that: (1) 25OHD repletion in insulin-resistant, overweight-to-obese persons was associated with reductions in subcutaneous adipose tissue expression of pro-inflammatory and profibrotic genes, decreased collagen immunofluorescence, and improved hepatic insulin sensitivity as well as worsening trends after six months on the placebo suggesting progressive metabolic effects of 25OHD deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding insulin secretion, beta cells express both VDR and 1 alpha-hydroxylase (Cyp27b1), which catalyzes the activation of 25OHD into 1,25(OH) 2 D, denoting the cell-intrinsic role for VDR [ 75 ]. Nevertheless, even if the relationship between vitamin D levels and islet function is significant, whether vitamin D supplementation can directly ameliorate insulin secretion in humans remains uncertain because intervention clinical trials have reported mixed results [ 75 , 76 , 77 , 78 ]. As regards the ubiquitous expression of VDR, and, in particular, in insulin-sensitive tissues, a study analyzing human and rodent data showed that: (1) 25OHD repletion in insulin-resistant, overweight-to-obese persons was associated with reductions in subcutaneous adipose tissue expression of pro-inflammatory and profibrotic genes, decreased collagen immunofluorescence, and improved hepatic insulin sensitivity as well as worsening trends after six months on the placebo suggesting progressive metabolic effects of 25OHD deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…79 In addition, it was interesting to find that vitamin D deficiency leads to decline in mitochondrial respiration, resulting in increasing reactive oxygen species (ROS) production, which in turn leads to decreased insulin signaling pathways and decreased GLUT4 gene transcription, leading to IR as well. 80 Whereas some clinical studies showed beneficial effect of vitamin D supplementation on improvement in insulin sensitivity, 81,82 other trials and a meta-analysis did not reveal any significant effect on glucose and insulin metabolism in obese [83][84][85] or overweight nondiabetic elderly subjects. 86…”
Section: Vitamin D Deficiency and Insulin Resistancementioning
confidence: 98%
“…In fact, insulin resistance seems to promote hypertension through the increase in sodium reabsorption in the renal tubules, the activation of the sympathetic nervous system, and the alteration of vascular resistance by increasing the concentration of calcium in smooth muscle cells [ 92 ]. Since it has been observed that vitamin D supplementation may reduce insulin resistance [ 93 ], treatment of this condition may be another mechanism by which vitamin D may help reduce blood pressure. According to this theory, a meta-analysis of 26 RCTs on diabetic patients showed that vitamin D supplementation was able to reduce systolic blood pressure values, especially in patients with vitamin D values below 50 nmol/L [ 94 ].…”
Section: Vitamin D and Erectile Dysfunction: Relationship With Blood ...mentioning
confidence: 99%
“…Finally, insulin resistance increases the production of LDL and triglycerides and reduces the synthesis of HDL [ 123 ]. As mentioned above, vitamin D might decrease insulin resistance counteracting this mechanism [ 93 ].…”
Section: Vitamin D and Erectile Dysfunction: Relationship With Hyperc...mentioning
confidence: 99%